Simulation On Performance Of Gan-Based Light Emitting Diodes With Varied Geometry And Contacts Design - Othman, Muhammad Firdaus (2010)
The main objective of this research is to minimize the current crowding problem inside GaN-based Light Emitting Diode (LED). Self heating effects and low radiative recombination are among the consequences that restrict the true potential of high electrical and optical performance of LED. By using device simulator, ISE TCAD as a tool, current crowding problem is investigated with varied geometries of lateral p-i-n LED structure. The effective lateral current paths between two contacts are examined by fixing the position of n-contact while p-contact position is varied on p-layer. This work revealed that the location of p-contact at the centre of p-type layer was the effective length of lateral current path where better current distribution and low series resistance were obtained due to the symmetry of current spreading length for carrier movement. Based on the effective lateral current path, the effect of contact geometrics showed that square shape contact out-performed other shape, namely hexagonal, octagonal and circular. The square shape which has largest contact periphery area helped current to spread uniformly and reduces the potential of current crowding at the n-contact due to lower resistance along the current path.